Drilling of Polymer-Matrix Composites - Krishnaraj, Vijayan; Zitoune, Redouane; Davim, J. Paulo (Manufacturing and Surface Engineering, 2013)
Polymeric composites are recognised as good candidates for structural components due to their inherent properties. However, they present several kinds of damages while creating holes for assembly. Delamination is considered the most serious damage since it reduces service life of the component. Thrust and delamination can be controlled by proper drill point geometry. Drilling at high speed is also a current requirement of the aerospace industry. This book focus on drilling of polymer matrix composites for aerospace and defence applications. The book presents introduction to machining of polymer composites and discusses drilling as a processing of composites.